Study on the Factors Influencing Consumer Buying Behaviour Among Individuals in Choosing Health Insurance Products - Prasant Kumar Rout, Prasanta Kumar Parida, (European Economic Letters (EEL), 2024)
Adage “Health is wealth” is universally acknowledged. But ensuring better health care for all is both a challenging as well costly affairs, especially with resource-crunched countries like India. However of many tools that can come very handy in funding the health care needs of the people is the concept of Insurance, which is contingent upon many individual as well as socio-economic factors. The present study examines all those factors that influence the behaviour of the buyer for individual health insurance products. The study was conducted in class one cities, by collecting data via a questionnaire method from a sample size of 150 respondents. The results were shown after analysis and interpreted with various statistical tools. It is observed from the results that there is still low level of awareness and less willingness to purchase health insurance products, in spite of unprecedented need that has been created by the recent covid19 pandemic. Various socio-economic indicators like literacy level, income level, marketing parameters etc and personal factors have a significant impact on the buying of individual health insurance.